PENGGUNAAN RADIOISOTOP PADA DETEKSI DINI PENYAKIT KANKER - Senduk, Pingkan; Danes, Vennetia R.; Rumampuk, Jimmy F. (e-Biomedik, 2015)
Abstract: Application of nuclear techniques, both the applications of radiation and radio-isotopes, are very useful since the use of atomic energy program for peaceful purposes was launched in 1953. Positron Emission Tomography (PET) is a new method for imaging the physiological functions of human tissues. Radiant energy emitted by a source of radiation can cause changes in terms of physical, chemical, and biological material in its path. Changes that occur can be controlled by choosing the type of radiation (or neutron) and regulate the dose absorbed, according to the effect needed to be achieved. Based on these properties, the radiation can be used directly such as in radiotherapy, and sterilization. In addition, the radiation emitted by a radioisotope, location and distribution can be detected from outside the body proper, and its activity can be measured accurately; therefore, the use of radioisotopes as tracer is very useful in metabolic studies, as well as tracking techniques and management or treatment of various organs, without having to perform surgery, particularly its use for early detection of cancer cells, or better known methods of cancer with PET.Keywords: radioisotopes, cancer, tracer, PETAbstrak: Aplikasi teknik nuklir, baik aplikasi radiasi maupun radio-isotop, sangat dirasakan manfaatnya sejak program penggunaan tenaga atom untuk maksud damai dilancarkan pada tahun 1953. Positron Emission Tomography (PET) merupakan metode terbaru untuk mencitrakan fungsi fisiologis jaringan tubuh manusia. Energi radiasi yang dipancarkan oleh suatu sumber radiasi dapat menyebabkan perubahan dari segi fisis, kimia dan biologi pada materi yang dilaluinya. Perubahan yang terjadi dapat dikendalikan dengan jalan memilih jenis radiasi (atau neutron) serta mengatur dosis terserap, sesuai dengan efek yang ingin dicapai. Berdasarkan sifat tersebut, radiasi dapat digunakan untuk penyinaran langsung seperti antara lain pada radioterapi, dan sterilisasi. Selain itu, radiasi yang dipancarkan oleh suatu radioisotop, lokasi dan distribusinya dapat dideteksi dari luar tubuh secara tepat, serta aktivitasnya dapat diukur secara akurat; sehingga penggunaan radioisotop sebagai perunut, sangat bermanfaat dalam studi metabolisme, serta teknik pelacakan dan penataan berbagai organ tubuh, tanpa harus melakukan pembedahan, khususnya dalam penggunaannya untuk mendeteksi dini sel kanker atau yang lebih dikenal penyakit kanker dengan metode PET.Kata kunci: radioisotop, penyakit kanker, perunut (tracer), PET